Some Mechanical Properties of Cement Treated Base (CTB) Incorporating Waste Portland Cement Concrete Under Different Corresponding Conditions - Khawla H. H. Shubber, Asst. Prof. Dr.; Sajjad Hashim Mohamed, Eng. (International Journal of Engineering and Technology, 2018)
This research represents a trial of understanding and improving mechanical properties of base or subbase granular materials, used in pavement construction, stabilized with Portland cement known as cement treated base (CTB) in terms of density, optimum water content (O.W.C), and compression Strength of three curing ages (3, 7, 28) days under different situations. Different Portland cement percent of (0, 5, 7, 10, 12, and 15) % by weight were added to selected base course granular materials (type B according to local standard specification in Iraq). Results showed that the density of mixture increase with increasing added cement percent, while O.W.C takes its maximum value around 7% cement content, and compression strength increase with increasing cement content and curing age. Then effect of replacing 50% of natural granular materials by waste Portland cement concrete (WPCC) was investigated on the results of (0, 7& 15)% cement content on density, O.W.C and compression strength in the three curing ages. Results reveled although density of mixture cooperating WPCC for 0% cement content was higher, CTB of natural granular material were denser. On the other hand compressive strength decrease in case of using WPCC for all percent cement added and curing ages. Finally, effect of soaking in water on CTB with (7 &15)% cement compressive strength of three curing ages was studied, under three period of soaking (1 week, 2 weeks, &one month). Test results exposed that, CTB Compressive strength increase with increasing soaking period but still less than that of un-soaked and for all curing ages. For each test stage mathematics relationships with acceptable correlation were presented proofing test results tendency.Â Â